Quantitative Volumetric Enamel Loss after Orthodontic Debracketing/Debonding and Clean-Up Procedures: A Systematic Review - Gaetano Paolone; Mauro Mandurino; Sofia Baldani; Maria Giacinta Paolone; Cecilia Goracci; Salvatore Scolavino; Enrico Gherlone; Giuseppe Cantatore; Giorgio Gastaldi (Applied Sciences, 2023)
Objectives: To conduct a systematic review assessing quantitative enamel loss occurring after orthodontic debonding and clean-up procedures. Materials and Methods: A systematic search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was performed on different databases (Embase, Medline, Scopus, Web of Science) for papers investigating volumetric enamel loss due to bracket and clear aligner attachment debonding and/or clean-up procedures. Studies investigating in vivo and in vitro articles published in the English language until 16 July 2022 were included. The study selection was then performed by two authors who screened the abstracts independently. Results: Of 421 screened abstracts, 41 articles were selected for full-text analysis. Finally, nine studies were included in this review. No in vivo papers were retrieved. In vitro papers investigated volumetric loss caused by the removal of metal brackets (n = 7), ceramic brackets (n = 1), and both (n = 1). The clean-up procedure varied among all investigations. Impressions at baseline and after debonding/clean-up were superimposed, and the volumes were subtracted using different 3D digital analysis software. Among all included studies, the volumetric loss of enamel ranged from 0.02 ± 0.01 mm3 to 0.61 ± 0.51 mm3 per tooth. Conclusions: Debonding and clean-up procedures produce enamel loss. The debonding/clean-up procedure that is able to cause the least enamel volume loss has yet to be identified.